Orthognathic surgery in Melnick–Needles syndrome: a review of the literature and report of two siblings. Issue 6 (June 2018) - O'Connell, J.E.; Bourke, B.; Kearns, G.J.
Abstract: Melnick–Needles syndrome (MNS) is a rare congenital X-linked dominant skeletal dysplasia, characterized by exophthalmos, a prominent forehead, and mandibular hypoplasia and retrognathism. Dental features may include anodontia, hypodontia, or oligodontia. Increased collagen content, unpredictable collagen synthesis, and abnormal bony architecture have raised concerns regarding bone splitting intraoperatively and bone healing postoperatively. This report describes the cases of two sisters with MNS, who successfully underwent orthognathic surgery consisting of bilateral mandibular ramus osteotomies combined with advancement genioplasty and iliac crest bone grafting, to correct the classical MNS facial deformity of mandibular retrognathia.